Cytokinins: Their Impact on Molecular and Growth Responses to Drought Stress and Recovery in Arabidopsis - Prerostova, Sylva; Dobrev, Petre I.; Gaudinova, Alena; Knirsch, Vojtech; Körber, Niklas; Pieruschka, Roland; Fiorani, Fabio; Brzobohatý, Břetislav; černý, Martin; Spichal, Lukas; Humplik, Jan; Vanek, Tomas; et al. (Frontiers in Plant Science, 2018)
Our phenotyping and hormonal study has been aimed to characterize the role of cytokinins (CK) in the drought and recovery responses of Arabidopsis thaliana. CK down-regulation was achieved by overexpression of the gene for CK deactivating enzyme cytokinin oxidase/dehydrogenase (CKX): constitutive (35S:CKX) or at the stress onset using a dexamethasone-inducible pOp/LhGR promoter (DEX:CKX). The 35S:CKX plants exhibited slow ontogenesis and higher expression levels of stress-associated genes, e.g. AtP5CS1, already at control conditions. CK down-regulation resulted during drought in higher stress tolerance (indicated by relatively low up-regulation of the expression of drought stress marker gene AtRD29B) accompanied with lower leaf water loss. Nevertheless, these plants exhibited slow and delayed recovery. CK levels were increased at the stress onset by stimulation of the expression of CK biosynthetic gene isopentenyl transferase (ipt) (DEX:IPT) or by application of exogenous CK meta-topolin. After water withdrawal, long-term CK elevation resulted in higher water loss in comparison with CKX transformants as well as with plants overexpressing ipt driven by senescence-inducible SAG12 promoter (SAG:IPT), which gradually enhanced CKs during the stress progression. In all cases, CK up-regulation resulted in fast and more vigorous recovery. All drought-stressed plants exhibited growth suppression associated with elevation of abscisic acid and decrease of auxins and active CKs (with the exception of SAG:IPT plants). Apart from the ipt overexpressers, also increase of jasmonic and salicylic acid was found.